2021
DOI: 10.4069/kjwhn.2021.03.15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the number of live births, maternal age at childbirth, and weight of live births between Korean women and immigrant women in 2018

Abstract: This study compared maternal age at childbirth, the number of live births, and the weight of live births between Korean women and immigrant women using statistical data from the Republic of Korea for the period of 2008-2018. Methods: The analysis was conducted using data from the Microdata Integrated Service of Statistics Korea (https://mdis.kostat.go.kr/index.do). Results: Korean women and immigrant women showed a higher age at childbirth in 2018 than in 2008. The percentage of newborns of Korean women with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, implementing a pregnancy and childbirth management method suitable for immigrant women in Korea could support having healthy children and reducing the IMR compared to the present statistic. A previous study confirmed the rates of preterm birth and low birth weight in immigrant and Korean women [6]. Therefore, the current study intended to compare the IMR, mortality-related features, and infant mortality factors of immigrant women with their Korean counterparts.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, implementing a pregnancy and childbirth management method suitable for immigrant women in Korea could support having healthy children and reducing the IMR compared to the present statistic. A previous study confirmed the rates of preterm birth and low birth weight in immigrant and Korean women [6]. Therefore, the current study intended to compare the IMR, mortality-related features, and infant mortality factors of immigrant women with their Korean counterparts.…”
Section: Introductionmentioning
confidence: 61%
“…The analysis of the infant mortality trends over 11 years revealed that the IMR in immigrant women was lower than that of Korean women; however, since 2015, the IMR of the two groups stands at a similar level. In particular, the IMR in immigrant women in 2018 was more than twice as high as than other years, but the birth rate of infants born to immigrant women in 2018 did not differ from that of previous years [6], i.e., the cycles of birth and death did not coincide. In Korea, the IMR for the past 5 years averaged 2.7, which is lower than the OECD average (4.2) [9], which illustrates the good management of maternal and child health in Korea.…”
Section: Discussionmentioning
confidence: 87%